Comparison of short term outcomes of open and laparoscopic cholecystectomy. Issue 1 (March 1995) - Cleary, R; Venables, C W; Watson, J; Goodfellow, J; Wright, P D
Abstract : OBJECTIVE–To compare the three month outcome of open and laparoscopic cholecystectomy. DESIGN–Prospective assessment of outcome for a series of patients encompassing the introduction of the laparoscopic technique. SETTING–One teaching hospital. PATIENTS–269 patients admitted for open cholecystectomy between January 1989 and March 1992 and 122 admitted for laparoscopic cholecystectomy between January 1991 and March 1992. MAIN MEASURES–Patients' reported symptoms and self assessed scores with the Nottingham health profile before operation and at three month follow up. Incidence of complications and adverse events after discharge. RESULTS–Similar improvements in symptom rates and health scores were seen regardless of surgical technique. A lower rate of postoperative complications was seen in the patients given laparoscopic surgery (6/95(6%) v 45/235(19%)), and their mean length of stay was lower (4.5 v 9.8 days). Similar results were obtained when the analysis was restricted to a subset of fairly uncomplicated cases (patients aged 60 or less without other illnesses on admission who were not undergoing emergency or urgent surgery), which constituted a larger proportion of the group given laparoscopy (35/95(37%) v 40/235(17%)). Between these two groups no significant difference was seen in the frequency of relevant readmissions to hospital or visits to general practitioners or accident and emergency departments. CONCLUSION–Ideally, a new surgical technique would be evaluated in a randomised trial. In the absence of such a trial, this observational study provides some evidence that the switch from open to laparoscopic cholecystectomy has brought benefits, particularly in terms of reduced length of stay in hospital. A range of clinical and patient derived indicators suggests that these gains have not been associated with a reduction in the quality of the outcome at three months.